The relationship between non-financial rewards and job satisfaction among support staff at Jabatan Laut Malaysia Wilayah Sarawak (JLMWSK)/ Mohd Syafiq Sapawi - Sapawi, Mohd Syafiq (2018)
The main purpose of this study is to identify is there any relationship between non-financial reward and job satisfaction. The study is conducted at Jabatan Laut Malaysia Wilayah Sarawak (JLMWSK) where 88 participants responded to the questionnaire. The result of this study found that, there is positive, significant and moderate relationship between job enrichment and job satisfaction (r=.377). There was difference relationship shown by recognition and job satisfaction where there is positive, significant and strong relationship between those variables (r=.614). As a result, it was found that support staff at JLMWSK preferred recognition than job enrichment where it satisfies them more to perform better. Therefore, the researcher recommended that the organization must implement job enrichment to the support staff to make them familiar with it and there is a chance to satisfy them with job enrichment.